Comprometimento cognitivo e sintomas depressivos em idosos em hemodiálise em Belo Horizonte, Minas Gerais, Brasil - Claudia Pacheco Caciquinho Vieira (2008)
Introduction: 25% of patients on hemodialysis are aged and this number tends to rise. We investigate cognitive impairment and symptoms of depression in elderly on hemodialysis. Methods: we evaluated 105 patients at the hospital Santa Casa de Belo Horizonte with the following tests: The Mini Mental State Examination, a Verbal Fluency Test, a Memory for Objects Test, the Pfeffer Functional Activities Questionnaire, the Katz Activities of Daily Living Index and the Geriatric Depression Scale. Results: patients were on hemodialysis for a mean of 46 months, were 69 years old average, male predominance. On average they had basic instruction (4 years or less) and dialysis adequacy (Kt/V > 1,2) warranted. The main causes of kidney disease were diabetes, ischemic renovascular disease and hypertension. Twenty one percent had physical limitations and 49,5% were functionally dependent (13,4% for basic activities). Forty nine percent self evaluated their health status as good or very good. Annual mortality was 13%, with dementia and low Kt/V as predictors. The frequency of cognitive impairment was 79% and of probably dementia 35%. Predictors were: cerebrovascular disease, albumin < 3,5 g/dL, depression, age and low family income. None of the medical charts presented a diagnosis of dementia. The frequency of depressive symptoms was 32%, but only 6% had a medical registry on the chart. They were predicted by alcoholism, functional dependency, cerebrovascular disease, gender (female) and younger age. Conclusion: cognitive impairment and symptoms of depression are common, under diagnosed and undertreated in elderly on hemodialysis. Vascular disease has an important hole in the genesis of these conditions. Physical impairment and functional dependency are also commons and signalizes depression, dementia and poor quality of life. Social support provided by hemodialysis team is important in this result when compared with elderly from the community